Addition of Nitazoxanide to PEG-IFN and Ribavirin to Improve HCV Treatment Response in HIV-1 and HCV Genotype 1 Coinfected Persons Naïve to HCV Therapy: Results of the ACTG A5269 Trial. Issue 6 (November 2013) - Amorosa, Valerianna K.; Luetkemeyer, Anne; Kang, Minhee; Johnson, Victoria A.; Umbleja, Triin; Haas, David W.; Yesmin, Suria; Bardin, Matthew C.; Chung, Ray T.; Alston-Smith, Beverly; Tebas, Pablo; Peters, Marion G.
Abstract : Background: We hypothesized that nitazoxanide (NTZ) added to pegylated interferon alfa-2a (PEG-IFN) and weight-based ribavirin (WBR) would improve hepatitis C virus (HCV) virologic responses in HCV treatment-naïve HIV-1/HCV genotype 1 coinfected persons.Methods: Prospective, single-arm study in which subjects received 4-week lead-in (NTZ 500 mg twice daily) followed by 48 weeks of NTZ, PEG-IFN, and WBR. We compared the HCV virologic responses of these subjects to historical controls from the completed ACTG study A5178 who received PEG-IFN and WBR and had similar subject characteristics. Primary endpoints were early virologic response and complete early virologic response (EVR and cEVR).Results: Among 67 subjects (78% male; 48% Black; median age, 50 years), EVR was achieved in 65.7% (90% CI, 55.0%–75.3%), cEVR in 38.8% (28.8%–49.6%). and SVR in 32.8% (23.4%–43.5%). EVR was higher with NTZ (51.4% in A5178; P = .03), but the sustained virologic response (SVR) proportion was similar (27.3% in A5178; P = .24). In contrast to A5178, SVR was similar across IL28B genotypes. Overall, NTZ was safe and well-tolerated.Conclusion: Whereas EVR proportion improved significantly in this pilot study, the addition of NTZ to PEG-IFN/WBR did not significantly improve SVR compared to historical controls. NTZ may be associated with an attenuation of the effect of IL28B on HCV treatment response.